Mengukir paradigma menembus tradisi : pemikiran tentang keserasian jender - Parawansa, Khofifah Indar, 1965- (Jakarta : LP3ES, 2006)
Social conditions and government policy on Indonesian women; collection of seminar papers and speeches by the former Minister for Women Empowerment.
Includes bibliographical references (p. [252]-256)
Keywords: Women in development -- Indonesia; Women -- Indonesia -- Social conditions; Women in politics -- Indonesia; Women -- Government policy -- Indonesia